Challenges and Opportunities for Sustainable Finance - Rotaru, Camelia S. Ferrua (The journal of contemporary issues in business and government, 2019)
With the move toward sustainability on the rise, significant challenges and opportunities arise as investors and analysts attempt to evaluate how companies incorporate ESG factors in their strategies in order to generate long-term competitive financial returns with positive societal impact. Since the current businesses landscape and reporting environment provides for limited, voluntary disclosures on ESG issues and rewards short-term performance, management is often reluctant to reallocate capital toward long-term sustainability goals and investors struggle to evaluate the impact of ESG factors on performance. Boards of directors are, therefore, uniquely positioned to develop and enact long- term business visions that clearly articulate the role that ESG factors play in the business and align current business performance with long-term sustainable finance factors. This would allow management to execute and forecast against objectives that address the strategic guidance given for the business and also provide a clearer sense of direction to analysts and investors as they evaluate the financial impact of ESG considerations.